2012
DOI: 10.1158/0008-5472.can-11-0210
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Ezrin Phosphorylation Prevents Metastasis and Alters Cellular Metabolism in Osteosarcoma

Abstract: Ezrin links the plasma membrane to the actin cytoskeleton where it plays a pivotal role in the metastatic progression of several human cancers (1, 2), however, the precise mechanistic basis for its role remains unknown. Here we define transitions between active (phosphorylated open) and inactive (dephosphorylated closed) forms of Ezrin that occur during metastatic progression in osteosarcoma. In our evaluation of these conformations we expressed C-terminal mutant forms of Ezrin that are open (phosphomimetic T5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…One of the advantages of the subpathway method is that it identifies more pathways than the traditional pathway enrichment. Using SubpathwayMiner, we found several metabolismrelated subpathways for the DEGs in this study, supporting recent findings about the relationship between Ezrin and cellular metabolism [26]. Ren et al found differentially expressed genes that obtained from mutant Ezrin overexpression in osteosarcoma were functionally linked to carbohydrate and amino acid metabolism.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One of the advantages of the subpathway method is that it identifies more pathways than the traditional pathway enrichment. Using SubpathwayMiner, we found several metabolismrelated subpathways for the DEGs in this study, supporting recent findings about the relationship between Ezrin and cellular metabolism [26]. Ren et al found differentially expressed genes that obtained from mutant Ezrin overexpression in osteosarcoma were functionally linked to carbohydrate and amino acid metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…Ren et al found differentially expressed genes that obtained from mutant Ezrin overexpression in osteosarcoma were functionally linked to carbohydrate and amino acid metabolism. In particular, cells expressing closed, inactive Ezrin exhibited reduced lactate production and basal or ATP-dependent oxygen consumption [26]. It suggests that the correlation between Ezrin and metabolism might be a common phenomenon in different cell type of cancers.…”
Section: Discussionmentioning
confidence: 94%
“…Disseminated metastatic cells encounter various microenvironmental stresses in the circulation or after reaching a new environment where they must adapt and endure these stresses to survive and establish secondary tumors (33,34). Studies using human and mouse osteosarcoma cells expressing inactive ezrin demonstrated that dysregulation of ezrin function results in a consistent increase in apoptosis of cells early after their arrival in the lung with no effect on the growth of primary tumor (35). In the present study, the comparison of global gene expression changes in response to NSC305787 and NSC668394 treatment indicated a common transcriptional regulation of genes with functional relevance to integrated stress response, suggesting a specific ezrin-mediated response in both human and mouse osteosarcoma cells (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that low metastatic tumor cells have lower oxygen consumption than high metastatic tumors, including osteosarcoma. 30,31 Although many studies reported a shift from oxidative phosphorylation to glycolysis to provide energy for cellular activities in cancer cells, 32 cancer cells have also been reported to rely on oxidative phosphorylation and mitochondrial bioenergetics pathways for anabolism and energy production. 33 Our present finding indicates that PP2A Cα is involved in the regulation of mitochondrial respiratory capacity.…”
Section: Discussionmentioning
confidence: 99%